A Case Study of Psychological Features of Children in Conflict with the Law in Violence and Sexual Offenses - Rihhadatul Aisy; Eriza Farizan Adani (International Conference on Psychology and Education (ICPE), 2025)
Adolescents in conflict with the law often have complex and stressful psychosocial backgrounds. This qualitative research uses a case study approach to understand the psychological dynamics of a child in conflict with the law through psychological assessment. The subject in this study was a 17-year-old male adolescent who was involved in a case of child abuse and sexual intercourse. Data were obtained through interviews, observations and aggression scales conducted during the coaching process at the X Social Protection and Rehabilitation Center. Additional information was obtained from interviews with people closest to the subject. The assessment results showed that the subject had difficulty in controlling aggressiveness, which was influenced by less affectionate and less supervised parenting, exposure to violence, and a social environment that did not support moral development. This research highlights the important role of family and social environment in shaping adolescent behavior. Albert Bandura's social learning theory explains that learning can occur through observation and modeling from the surrounding environment. This study concluded that the subject's deviant behavior was influenced by a lack of parental affection, a history of physical abuse, and a negative peer environment.